Прикраси скіфського часу населення Лісостепу: вступ до теми за матеріалами Дніпровського Лівобережжя - Ходукіна, Ю.М. (Археологія і давня історія України, 2021)
У статті проведено огляд сучасного стану досліджень прикрас Лісостепової Скіфії за матеріалами
пам’яток Дніпровського Лівобережжя. Висвітлюється історія їх вивчення, зокрема із залученням світової
практики. На прикладі відомих зразків шпильок та
сережок описується специфіка дослідження прикрас з
різних типів пам’яток, розглядаються питання типології та технології виготовлення. This paper focuses on the pins and earrings as the
most popular and diverse type of Scythian jewelry.
They are exactly the chronological and cultural markers
used by researchers in the reconstruction of migrations
and connections of the forest-steppe population.
The adornments in ancient times, as well as nowadays,
were one of the main cultural and social identity markers.
First, they have been studied both in the context of the
Scythian material remnants and the unique local variants.
Vladimira Petrenko was one of the first who made the typology
of these artifacts which led to the change in the field.
Soon, new findings were discovered that developed the typology
of the artifacts, which was based on the local variants
and peculiar decorations, e. g. earrings. The common
feature of the modern research is to lessen the number of
taxa in the typological scheme and determine the precise
and rare indicators of the type origin. Even though the
adornment of Scythian Age were studied just as a part of
the material culture, the consensus of the academia shows
that jewelries can represent a wide range of social and cultural
processes in ancient communities.
Usually, the Scythian adornments are found in the
burial and settled sites. Such material remnants combined
with the anthropological data and certain fixation
can enlarge our understanding of the usage and
function of these artifacts. Furthermore, they give us
knowledge of the possible popular costume of the time,
the sex and age differences in fashion. In addition, new
finds from the settlements widen the source base. The
analysis of the jewelries in the context of the settlement
structures gives a more precise chronology and
modes of production. Today, it is sure that the main
three technological methods were welding, casting,
and smiting. Each method related to the distinct forms
and metals the item was made of.